Conidiobolus srinivasanii (Conidiobolaceae, Entomophthorales), a novel species from Western Ghats, Maharashtra, India - Pawar, Kadambari S.; Singh, Paras N.; Singh, Sanjay K. (Phytotaxa, 2025)
The genus Conidiobolus represents fungi of ecological and pathological importance, recently undergoing significant taxonomic revisions driven by molecular advancements. This study describes Conidiobolus srinivasanii sp. nov., a saprobic species isolated from plant litter in Maharashtra, India. Morphological examinations reveal unique features, such as vasiform primary conidiophores, catenate secondary conidia, and multipolar germ tube development, distinguishing it from closely related species. Multigene phylogenetic study (TEF-1α, mtSSU, nucLSU) substantiates its placement within Conidiobolus s.s. while emphasizing genetic divergence from other species. This work integrates morphological observations with genomic data to improve understanding of the taxonomy of this newly described species and underscores the significance of plant litter as a crucial habitat for fungal diversity. These findings aid in the continual refinement of fungal classification and elucidation of the evolutionary complexity of the genus.